2020
DOI: 10.3390/ijerph17217961
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Role of Society and Firms to COVID-19 Management among Medical Practitioners

Abstract: Measurement of job stress and employees’ commitment are few of the admired topics in the corporate world amongst business writers. With a principal aim to trial the blow of exposure to COVID-19 patients on doctors’ job stress and commitment, in Pakistan; data have been collected through 7-10 min telephonic interview from voluntary participants and a sample of 129 responses were analyzed by Structure Equation Modeling-Partial Least Square (SEM-PLS) path modeling through Smart PLS 3.2. The results of the study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 55 publications
(69 reference statements)
6
52
0
Order By: Relevance
“…Their minimization in this respect requires a new approach to systemic risk management which includes pandemic risk. The time and manner of responding to the spread of the virus in individual countries of the European Union has caused complex and widespread negative economic consequences which are shaping the current direction of development of social and economic processes [ 54 , 55 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their minimization in this respect requires a new approach to systemic risk management which includes pandemic risk. The time and manner of responding to the spread of the virus in individual countries of the European Union has caused complex and widespread negative economic consequences which are shaping the current direction of development of social and economic processes [ 54 , 55 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The perceived stress during a Covid-19 epidemic in Pakistan is discussed with mental health and emotional (Nanjundaswamy, Pathak, & Chaturvedi, 2020 ), psychological impact (Qureshi et al, 2020 ), level of knowledge, attitude, practice (Jawed, Manazir, Zehra, & Riaz, 2020 ), employees’ commitment (Zandi, Shahzad, Farrukh, & Kot, 2020 ), and psychological distress (Abid et al, 2020 ). We believe that most studies were limited to detection or diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The explosion of Ebola in West Africa in 2014 took a heavy toll on people and had a debilitating impact on public psychology [16,17]. Not only do people who experience traumatic events develop psychological symptoms, but also those who have been exposed to or associated with trauma experience varying degrees of psychological trauma, including post-traumatic stress disorder, melancholia, and depression [18][19][20]. Ample evidence has shown that psychological disorders (e.g., depression and anxiety) affect quality of life and physical and mental health [10,21,22].…”
Section: Introductionmentioning
confidence: 99%